Characters and Protein Profile in the First Stage of Mud Crab (Scylla serrata) Infected by Red Sternum Syndrome - Srimeetian, Pattarawadee; Tunkijjanukij, Suriyan (Journal of Mahanakorn Veterinary Medicine, 2016)
The first stage of mud crabs infected by red sternum symptom and normal mud crabs were collected from a farm in Samut Songkhram province, Thailand and their used to study in external-internal morphological characterization and their behavior. The symptoms of red sternum syndrome showed orange color of abdominal thorax, black spots on joints and very thin carapace. In internal organs were dark and soft as well as bitter meats. The behavior of mud crab were normal feeding and moving at 1st to 3rd day after infected by the syndrome. While 4th to 7th day after infected found that mud crabs were lose appetite and limited moving. The color blood of those crabs were classified into two groups; orange-blue (group I: 1st to 3rd day) and orange (group II: 4th to 7th day). To determine the protein expression of red sternum and normal mud crabs using Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS PAGE) found that during 1st to 3rd day after red sternum syndrome infection demonstrated that the pattern of proteins were same as normal crab, while 4th to 7th day after infection showed that the additional protein was found compared to normal mud crab, approximately 137 kDa.